2001
DOI: 10.1128/mcb.21.1.156-163.2001
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of ETO Is Obligatory for Corepressor Interaction

Abstract: Nearly 40% of cases of acute myelogenous leukemia (AML) of the M2 subtype are due to a chromosomal translocation that combines a sequence-specific DNA binding protein, AML1, with a potent transcriptional repressor, ETO. ETO interacts with nuclear receptor corepressors SMRT and N-CoR, which recruit histone deacetylase to the AML1-ETO oncoprotein. SMRT-N-CoR interaction requires each of two zinc fingers contained in C-terminal Nervy homology region 4 (NHR4) of ETO. However, here we show that polypeptides contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 54 publications
(79 reference statements)
11
104
1
Order By: Relevance
“…However, we observed that the AML1-ETO(DNHR2)/DNA complex moved much faster than that of the AML1-ETO(DNHR34) (Figure 1e,upper panel). As the molecular mass of AML1-ETO(DNHR2) is greater than that of AML1-ETO(DNHR34) (Figure 1e, bottom panel), these results suggest that while AML1-ETO and AML-ETO(DNHR34) bind the AML1 consensus sequence as a dimer, AML1-ETO(DNHR2) most likely binds to this element as a monomer, in agreement with the NHR2 domain of ETO being responsible for the formation of AML1-ETO homodimer (Minucci et al, 2000;Zhang et al, 2001;Davis et al, 2003).…”
Section: Aml1mentioning
confidence: 57%
See 4 more Smart Citations
“…However, we observed that the AML1-ETO(DNHR2)/DNA complex moved much faster than that of the AML1-ETO(DNHR34) (Figure 1e,upper panel). As the molecular mass of AML1-ETO(DNHR2) is greater than that of AML1-ETO(DNHR34) (Figure 1e, bottom panel), these results suggest that while AML1-ETO and AML-ETO(DNHR34) bind the AML1 consensus sequence as a dimer, AML1-ETO(DNHR2) most likely binds to this element as a monomer, in agreement with the NHR2 domain of ETO being responsible for the formation of AML1-ETO homodimer (Minucci et al, 2000;Zhang et al, 2001;Davis et al, 2003).…”
Section: Aml1mentioning
confidence: 57%
“…It was reported that removal of the NHR2 domain diminished the ability of AML1-ETO to block hematopoietic differentiation of U937 cells (Zhang et al, 2001;Hug et al, 2002). Sin3 is directly dependent on this domain for interactions with ETO, whereas corepressors for nuclear hormone receptor, SMRT and NCoR, are indirectly dependent on this domain to facilitate interactions with the NHR4 domain of ETO (Zhang et al, 2001). In the studies reported here, we demonstrated that the NHR2 domain of ETO was responsible for the reduction of intranuclear mobility of AML1-ETO, which is reminiscent of that for NuMARARa, in which the coiled-coil domain of NuMA was found to be responsible for the mobility reduction of NuMA-RARa .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations